Holding space with insomnia - Hopland Guidi, Shelby (Murmurations: Journal of Transformative Systemic Practice, 2023)
Exegesis Like so many in my community, and around the world, I experienced COVID-19 – as a community member, as a student, and as someone who contacted the virus. While navigating the illness was difficult, for me the aftermath, and the arrival of insomnia as a symptom of Long COVID-19 is where my story begins. I was a Master of Social Work student, integrating my learnings into practice to become a therapist. I had to learn how to show up authentically and with competence, while having not slept, sometimes for days. Walking this line so often invited the question: How can I show up fully, when I am so empty? Beyond being able to show up, how could I hold space for all my family’s stories of COVID-19, while simultaneously having such a predominant story myself. Now, a year later, this poem is my journey of building an ongoing relationship with insomnia and my COVID-19 story so that I may hold my family’s stories as a family therapist – and for both to be tended to with gentleness and love.